2021
DOI: 10.1159/000519445
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Mediterranean Diet on the Gut Microbiome in Healthy Human Subjects: A Pilot Study

Abstract: <b><i>Background and Aims:</i></b> Despite the reported salutary benefits of a Mediterranean diet (MD) on a wide variety of health conditions, the specific microbial changes associated with an MD within the gastrointestinal (GI) tract are not well studied. Specifically, although population and survey-based studies have shown microbial changes, there are no published data on how an MD alters the gut flora in a controlled setting. <b><i>Methods:</i></b> We recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…The main factors influencing structure are diet, exercise, stress, disease and medications [ 9 ]. It is generally accepted that a Mediterranean diet rich in fruit, vegetables, nuts, fermented foods and fish yields an optimal microbiota [ 10 ]. Up to 80% of medications prescribed by clinicians impact the gut microbiota, and many in a negative manner [ 11 ].…”
Section: Microbiota Structurementioning
confidence: 99%
“…The main factors influencing structure are diet, exercise, stress, disease and medications [ 9 ]. It is generally accepted that a Mediterranean diet rich in fruit, vegetables, nuts, fermented foods and fish yields an optimal microbiota [ 10 ]. Up to 80% of medications prescribed by clinicians impact the gut microbiota, and many in a negative manner [ 11 ].…”
Section: Microbiota Structurementioning
confidence: 99%
“…A future direction in the food industry can be functional food, which shapes the intestinal microbiota to a health-promoting composition. A varied, homemade, fruit- and vegetable-rich Mediterranean diet has similar health-promoting effects on the microbiota ( 179 181 ).…”
Section: Effects Of Nutrition On Intestinal Permeability and The Gut ...mentioning
confidence: 99%
“…Homeostasis of intestinal bacteria is crucial for maintaining the health of the host. However, the gut flora is susceptible to changes in host age, diet, and exercise 37‐39 . At present, a large number of studies have suggested that intestinal bacteria may be involved in the pathogenesis of neurodegenerative diseases, such as Alzheimer's disease, amyotrophic lateral sclerosis, and PD 40‐42 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the gut flora is susceptible to changes in host age, diet, and exercise. 37 , 38 , 39 At present, a large number of studies have suggested that intestinal bacteria may be involved in the pathogenesis of neurodegenerative diseases, such as Alzheimer's disease, amyotrophic lateral sclerosis, and PD. 40 , 41 , 42 Furthermore, changed intestinal microecology has also been observed in patients with diseases associated with PD, such as diabetes and colitis.…”
Section: Introductionmentioning
confidence: 99%